2022
DOI: 10.1039/d1tc05734k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and luminescence of Cs2HfCl6 micro- and Cs2HfF6 nanoparticles

Abstract: Hafnium-based halide crystals are attractive wide-bandgap phosphor materials for scintillation applications due to their high density, low hygroscopicity and bright radioluminescence. Here, we describe synthetic approaches towards the formation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Fellner and Lauria recently observed a broad emission centered at 489 nm from CHF without a prominent peak, which was considered as defect-related luminescence. [35] The broad emissions observed here have different characters, which are similar to the broad emissions from STEs as reported in the CHC host in the literature. [15][16][17][18][19] The STE emission is centered at 452 nm in CHC.…”
Section: Photoluminescencesupporting
confidence: 83%
See 2 more Smart Citations
“…Fellner and Lauria recently observed a broad emission centered at 489 nm from CHF without a prominent peak, which was considered as defect-related luminescence. [35] The broad emissions observed here have different characters, which are similar to the broad emissions from STEs as reported in the CHC host in the literature. [15][16][17][18][19] The STE emission is centered at 452 nm in CHC.…”
Section: Photoluminescencesupporting
confidence: 83%
“…It is shown that CHF is the most stable one based on its lowest enthalpy of formation in this series of compounds, which was supported experimentally by Fellner and Lauria recently that CHF has higher thermal stability than CHC. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The weak excitation band in the range of 300 nm to 400 nm and the emission band at 570 nm of Cs 2 ZrCl 6 might be originated from sub-band gap defects owing to the Zr 4+ or Cl À vacancies, which are similar to Cs 2 HfX 6 (X = F, Cl) nanocrystals and Cs 2 TiI 6 . 17,25,26 The reasons are as follows: (1) as Zr, Hf and Ti belong to the group IV elements and have similar chemical characteristics, Cs 2 ZrCl 6 may also be a defectintolerant semiconductor, which is similar to Cs 2 TiI 6 and Cs 2 HfX 6 (X = F, Cl). Therefore, the defect level produced by the Zr 4+ and Cl À vacancies might occur deep in the band gap and localize potential mobile charge carriers.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…30,31 Additionally, according to the Kubelka-Munk function and the Tauc relationship, the direct optical band gap of Cs 2 ZrCl 6 was calculated to be 2.78 eV; (3) as reported in Cs 2 HfF 6 nanopowders, doping Eu 3+ or Mn 2+ did not produce the characteristic emission of doped ions, but increased the emission intensity of defects in Cs 2 HfF 6 , which is due to an increase in defects thanks to the difference in charge between Hf 4+ and Eu 3+ / Mn 2+ . 26 Hence, we synthesized a series of Cs 2 ZrCl 6 :M (M = Ho 3+ , Tm 3+ , Dy 3+ , Er 3+ , Mn 2+ ) to further confirm the existence of defects and the influence of different ions on defects. As shown in Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%